FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK DI BURSA EFEK INDONESIA - Hani Andharini; Annisa Kanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence about the variables that affecting tax avoidance. The independent variables in this research are leverage, firm size, profitability, sales growth, proportion of independent commissioners, and audit quality. While the dependent variable in this research is tax avoidance. The object used in this research are manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. The amount of samples that used are 57 companies with 171 data used purposive sampling method. The method that has been used affected between independent variable and dependent variable tax avoidance is multiple regression method. The result of this research showed that leverage affecting tax avoidance. Whereas leverage, firm size, sales growth, proportion of independent commissioners, and audit quality did not affect Tax Avoidance.